Answer: (-3,19)
Step-by-step explanation:
Here the given function is,
[tex]y = -2x^2-12x+1[/tex]
[tex]\implies y = -2(x^2+6x)+1[/tex]
[tex]\implies y = -2(x^2+6x)+1+18-18[/tex]
[tex]\implies y = -2(x^2+6x+9)+19[/tex]
[tex]\implies y = -2(x+3)^2+19[/tex]
[tex]\implies y = -2(x-(-3))^2+19[/tex]
Since, the standard equation of a quadratic function is [tex]y = a(x - h)^2 + k[/tex]
Where (h,k) is the vertex of the function.
On comparing the equation of given function with this standard form,
We get, the vertex of the given function is (-3,19)
⇒ First option is correct.